On stack-augmented polyautomata - Kutrib, Martin; Justus Liebig University Giessen (My University, 1995)
A stack augmented generalization of cellular automata, the pushdown cellular automata, are investigated. We are studying the language accepting capabilities of such devices. Closure properties of realtime, lineartime and unrestricted time language families are shown. The relationships of these families with each other and to languages of sequential automata are considered.
Keywords: ddc:004